A method for preparing a ceramic insulator

By preparing ceramic insulators with thiourea intercalation bimetallic oxide and glass powder, the problem of insulator flickering is solved, the photocatalytic self-cleaning and anti-fouling performance of ceramic insulators is achieved, and the safety and stability of transmission lines are improved.

CN119330596BActive Publication Date: 2025-03-18HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411908920.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Insulator flickering is a major accident facing the power system and seriously threatens the safe operation of the power system. How to improve the anti-flickering performance of the insulator is of great significance.

Method used

Using a method of preparing ceramic insulators, a layered bimetallic oxide, glass powder, sodium tungstate, ferrous sulfate and deionized water ball mill are mixed evenly, and a binder is added to obtain a glaze, and sintered on the ceramic substrate to generate a ceramic insulator with photocatalytic activity and anti-fouling flash properties.

Benefits of technology

The photocatalytic self-cleaning performance and anti-fouling flash performance of ceramic insulators can effectively reduce the maintenance cost of transmission lines and ensure the safe and stable operation of transmission lines.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of insulating materials, and in particular to a method for preparing a ceramic insulator. The method comprises the following steps of: uniformly mixing cryolite, kaolin, quartz, thiourea intercalated layered bimetallic oxide, glass powder, sodium tungstate, ferrous sulfate and deionized water by ball milling, adding a binder and stirring evenly to obtain a glaze, applying the glaze to a ceramic substrate to obtain a rough blank, drying the rough blank, placing the rough blank in a muffle furnace, heating the temperature to 1100-1200° C., and sintering the rough blank for 1-5 hours. The ceramic insulator prepared by the invention has excellent photocatalytic self-cleaning performance and anti-pollution flashover performance, can ensure the safe and stable operation of a power transmission line, and reduce the maintenance cost of the line operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of insulating materials, in particular to a method for preparing a ceramic insulator. Background Art

[0002] Insulator flashover is an operation accident with large-scale destructive capability faced by power systems, which seriously threatens the safe operation of power systems. According to statistics, the number of insulation flashover accidents caused by flashover in power grid accidents is second only to lightning accidents, while the losses caused by flashover accidents are far greater than those caused by lightning accidents. How to improve the anti-flashover performance of insulators is of great significance to ensure the safe and stable operation of transmission lines and reduce the maintenance cost of line operation. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a method for preparing a ceramic insulator.

[0004] The technical solutions adopted are as follows:

[0005] A method for preparing a ceramic insulator:

[0006] Cryolite, kaolin, quartz, thiourea intercalated layered bimetallic oxide, glass powder, sodium tungstate, ferrous sulfate and deionized water are ball-milled and mixed evenly, and then a binder is added and stirred to obtain a glaze, and the glaze is applied to a ceramic substrate to obtain a rough blank, and after the rough blank is dried, it is placed in a muffle furnace and heated to 1100-1200°C and sintered for 1-5 hours;

[0007] The preparation method of the thiourea intercalated layered bimetallic oxide is as follows:

[0008] The layered bimetallic oxide is added to a mixed solvent consisting of dimethyl sulfoxide and deionized water, and the mixture is sealed and heated to 100-110°C and stirred for reaction for 1-5 hours. After the reaction is completed, the precipitate is collected, washed, and dried to obtain a dimethyl sulfoxide intercalated layered bimetallic oxide, which is added to methanol and stirred for reaction for 5-10 days to obtain a methanol intercalated layered bimetallic oxide. Finally, the methanol intercalated layered bimetallic oxide is added to a saturated thiourea methanol solution and reacted in a water bath for 10-20 hours. After the reaction is completed, the product is collected, washed, and freeze-dried at low temperature;

[0009] The layered bimetallic oxide is a Zn-Al layered bimetallic oxide or a Cu-Al layered bimetallic oxide.

[0010] Furthermore, the glaze is prepared from the following raw materials in parts by weight:

[0011] 10-15 parts of cryolite, 20-30 parts of kaolin, 10-15 parts of quartz stone, 5-10 parts of thiourea intercalated layered bimetallic oxide, 5-10 parts of glass powder, 5-10 parts of sodium tungstate, 1-5 parts of ferrous sulfate, 5-10 parts of binder, and 40-60 parts of deionized water.

[0012] Furthermore, the volume ratio of dimethyl sulfoxide to deionized water is 10-20:1.

[0013] Furthermore, the preparation method of the layered bimetallic oxide is as follows:

[0014] Add water-soluble zinc salt or water-soluble copper salt, water-soluble aluminum salt to deionized water, add alkaline precipitant to adjust the pH value of the system to 7-10, seal and heat to 110-130°C for hydrothermal reaction for 5-10h, collect the precipitate, wash and dry to obtain a precursor, place the precursor in a muffle furnace, heat to 500-600°C and calcine for 1-5h.

[0015] Furthermore, the glass powder is prepared from CaO, Al2O3, SiO2, and Bi2O3 in a mass ratio of 5-10:10-15:30-35:1-5.

[0016] Furthermore, the preparation method of the glass powder is as follows:

[0017] Mix CaO, Al2O3, SiO2 and Bi2O3 and grind them together. Heat them until they are melted to obtain a clear glass melt. Pour the glass melt into deionized water to obtain glass particles. Dry the glass particles and grind them together. Then, pass them through a 400-mesh sieve.

[0018] Furthermore, the binder is carboxymethyl cellulose and / or polyvinyl alcohol.

[0019] Furthermore, the heating rate during sintering is 1-10°C / min.

[0020] Beneficial effects of the present invention:

[0021] The present invention provides a method for preparing a ceramic insulator. Sodium tungstate and ferrous sulfate generate FeWO4 with photocatalytic activity in situ during sintering. The layered bimetallic oxide, as a sintering aid, can improve the microscopic morphology of the glaze and improve its hydrophobicity. On the other hand, the present application refers to the method of thiourea intercalation kaolin in the prior art, and uses a three-step intercalation substitution method to intercalate thiourea on the layered bimetallic oxide. During the sintering process, thiourea decomposes and reacts to generate metal sulfides. The metal sulfides construct a heterostructure with FeWO4 to inhibit photogenerated electrons. The compound of Bi2O3 and hole pairs can improve the visible light catalytic efficiency and realize the efficient degradation of organic pollutants. The glass powder as an inorganic binder can improve the bonding strength between the glaze and the ceramic matrix and increase the hardness of the glaze. The introduction of Bi2O3 can reduce the softening temperature and improve the fluidity of the glass powder during sintering, thereby better improving the microscopic morphology of the glaze and achieving a better reinforcement effect. The ceramic insulator prepared by the present invention has excellent photocatalytic self-cleaning performance and anti-pollution flashover performance, which can ensure the safe and stable operation of the transmission line and reduce the maintenance cost of the line operation. DETAILED DESCRIPTION

[0022] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0023] Embodiment 1:

[0024] A method for preparing a ceramic insulator:

[0025] S1: Weigh the following raw materials in parts by weight: 15 parts of cryolite, 25 parts of kaolin, 10 parts of quartz stone, 8 parts of thiourea intercalated Cu-Al layered bimetallic oxide, 5 parts of CASB glass powder, 10 parts of sodium tungstate, 5 parts of ferrous sulfate, 5 parts of carboxymethyl cellulose, and 50 parts of deionized water;

[0026] S2: Add cryolite, kaolin, quartz, thiourea intercalated Cu-Al layered bimetallic oxide, CASB glass powder, sodium tungstate, ferrous sulfate and deionized water into a ball mill, mix and ball mill on a planetary ball mill for 10 hours, then add a binder carboxymethyl cellulose, stir at a speed of 120r / min for 10 minutes to obtain a glaze, apply the glaze on a 95 alumina ceramic substrate (XP-70 disc suspension) to obtain a rough blank with a coating thickness of 10±1μm, dry the rough blank in an oven at 60℃ for 10 hours, put it in a muffle furnace, heat it to 1150℃ at a speed of 5℃ / min, sinter it for 2 hours to form a glaze surface, and then take it out.

[0027] The preparation method of thiourea intercalated Cu-Al layered bimetallic oxide is as follows:

[0028] 45.3 g of copper nitrate trihydrate and 23.4 g of aluminum nitrate nonahydrate were added to 500 ml of deionized water and stirred to mix evenly. 13.3 g of sodium carbonate was dissolved in 500 ml of deionized water to obtain an alkaline precipitant. The alkaline precipitant was slowly added dropwise to the reaction system to adjust the pH to 9. After the addition, the system was sealed and heated to 110° C. for hydrothermal reaction for 8 h. After the reaction, the system was restored to room temperature. The precipitate was collected and washed thoroughly with anhydrous ethanol and deionized water. The precursor was dried in a 60° C. oven for 24 h to obtain a precursor. The precursor was placed in a muffle furnace and heated to 550° C. at a rate of 5° C. / min and calcined for 3 h to obtain a Cu-Al layered bimetallic oxide. 5 g of Cu-Al layered bimetallic oxide was added into a mixed solvent consisting of 600 ml of dimethyl sulfoxide and 60 ml of deionized water, sealed and heated to 110°C, stirred and reacted for 4 hours. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol and deionized water, and then dried in an oven at 60°C for 24 hours to obtain dimethyl sulfoxide intercalated Cu-Al layered bimetallic oxide, which was added into 500 ml of methanol and stirred and reacted for 7 days to obtain methanol intercalated Cu-Al layered bimetallic oxide. Finally, the methanol intercalated Cu-Al layered bimetallic oxide was added into 500 ml of saturated thiourea-methanol solution, and reacted for 15 hours in a 50°C water bath. After the reaction, the product was collected, washed thoroughly with anhydrous ethanol and deionized water, and then freeze-dried at low temperature.

[0029] The preparation method of CASB glass powder is as follows:

[0030] CaO, Al2O3, SiO2 and Bi2O3 in a mass ratio of 5:15:35:2 are added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is mixed and ball-milled on a planetary ball mill for 10 hours and then dried. The obtained mixture is added to a crucible, and the temperature is raised to 1200°C to melt and keep warm for 2 hours to obtain a clarified glass melt. The glass melt is poured into deionized water to obtain glass particles. The glass particles are dried and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is mixed and ball-milled on a planetary ball mill for 10 hours and then dried through a 400-mesh sieve.

[0031] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of glaze was added to 100ml (10mg / L) of methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 99.3%.

[0032] Embodiment 2:

[0033] A method for preparing a ceramic insulator:

[0034] S1: Weigh the following raw materials in parts by weight: 15 parts of cryolite, 25 parts of kaolin, 10 parts of quartz stone, 8 parts of thiourea intercalated Zn-Al layered bimetallic oxide, 5 parts of CASB glass powder, 10 parts of sodium tungstate, 5 parts of ferrous sulfate, 5 parts of carboxymethyl cellulose, and 50 parts of deionized water;

[0035] S2: Add cryolite, kaolin, quartz, thiourea intercalated Zn-Al layered bimetallic oxide, CASB glass powder, sodium tungstate, ferrous sulfate and deionized water into a ball mill, mix and ball mill on a planetary ball mill for 10 hours, then add a binder carboxymethyl cellulose, stir at a speed of 120r / min for 10 minutes to obtain a glaze, apply the glaze on a 95 alumina ceramic substrate (XP-70 disc suspension) to obtain a rough blank with a coating thickness of 10±1μm, dry the rough blank in an oven at 60℃ for 10 hours, put it in a muffle furnace, heat it to 1150℃ at a speed of 5℃ / min, sinter it for 2 hours to form a glaze surface, and then take it out.

[0036] The preparation method of thiourea intercalated Zn-Al layered bimetallic oxide is as follows:

[0037] 55.79g of zinc nitrate hexahydrate and 23.4g of aluminum nitrate nonahydrate were added to 500ml of deionized water and stirred to mix evenly. 13.3g of sodium carbonate was dissolved in 500ml of deionized water to obtain an alkaline precipitant. The alkaline precipitant was slowly added dropwise to the reaction system to adjust the pH to 9. After the addition, the system was sealed and heated to 110°C for hydrothermal reaction for 8h. After the reaction, the system was restored to room temperature. The precipitate was collected and washed thoroughly with anhydrous ethanol and deionized water. The precursor was dried in a 60°C oven for 24h to obtain a precursor. The precursor was placed in a muffle furnace and heated to 550°C at a rate of 5°C / min and calcined for 3h to obtain a Zn-Al layered bimetallic oxide. 5g of The Zn-Al layered bimetallic oxide was added to a mixed solvent consisting of 600 ml of dimethyl sulfoxide and 60 ml of deionized water, sealed and heated to 110°C, stirred and reacted for 4 hours. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol and deionized water, and then dried in an oven at 60°C for 24 hours to obtain dimethyl sulfoxide intercalated Zn-Al layered bimetallic oxide, which was added to 500 ml of methanol and stirred for reaction for 7 days to obtain methanol intercalated Zn-Al layered bimetallic oxide. Finally, the methanol intercalated Zn-Al layered bimetallic oxide was added to 500 ml of saturated thiourea-methanol solution, and reacted in a 50°C water bath for 15 hours. After the reaction, the product was collected, washed thoroughly with anhydrous ethanol and deionized water, and then freeze-dried at low temperature.

[0038] The preparation method of CASB series glass powder is the same as that in Example 1.

[0039] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 98.1%.

[0040] Embodiment 3:

[0041] A method for preparing a ceramic insulator:

[0042] S1: Weigh the following raw materials in parts by weight: 15 parts of cryolite, 30 parts of kaolin, 15 parts of quartz stone, 10 parts of thiourea intercalated Cu-Al layered bimetallic oxide, 10 parts of CASB glass powder, 10 parts of sodium tungstate, 5 parts of ferrous sulfate, 10 parts of carboxymethyl cellulose, and 60 parts of deionized water;

[0043] S2: Add cryolite, kaolin, quartz, thiourea intercalated Cu-Al layered bimetallic oxide, CASB glass powder, sodium tungstate, ferrous sulfate and deionized water into a ball mill, mix and ball mill on a planetary ball mill for 10 hours, then add a binder carboxymethyl cellulose, stir at a speed of 120r / min for 10 minutes to obtain a glaze, apply the glaze on a 95 alumina ceramic substrate (XP-70 disc suspension) to obtain a rough blank with a coating thickness of 10±1μm, dry the rough blank in an oven at 60℃ for 10 hours, put it in a muffle furnace and heat it to 1200℃ at a speed of 10℃ / min, sinter it for 5 hours to form a glaze surface, and then take it out.

[0044] The preparation methods of thiourea intercalated Cu-Al layered bimetallic oxide and CASB series glass powder are the same as those in Example 1.

[0045] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of the dried glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 98.9%.

[0046] Embodiment 4:

[0047] A method for preparing a ceramic insulator:

[0048] S1: Weigh the following raw materials in parts by weight: 10 parts of cryolite, 20 parts of kaolin, 10 parts of quartz stone, 5 parts of thiourea intercalated Cu-Al layered bimetallic oxide, 5 parts of CASB glass powder, 5 parts of sodium tungstate, 1 part of ferrous sulfate, 5 parts of carboxymethyl cellulose, and 40 parts of deionized water;

[0049] S2: Add cryolite, kaolin, quartz, thiourea intercalated Cu-Al layered bimetallic oxide, CASB glass powder, sodium tungstate, ferrous sulfate and deionized water into a ball mill, mix and ball mill on a planetary ball mill for 10 hours, then add a binder carboxymethyl cellulose, stir at a speed of 120r / min for 10 minutes to obtain a glaze, apply the glaze on a 95 alumina ceramic substrate (XP-70 disc suspension) to obtain a rough blank with a coating thickness of 10±1μm, dry the rough blank in an oven at 60℃ for 10 hours, put it in a muffle furnace, heat it to 1100℃ at a speed of 1℃ / min, sinter it for 1 hour to form a glaze surface, and then take it out.

[0050] The preparation methods of thiourea intercalated Cu-Al layered bimetallic oxide and CASB series glass powder are the same as those in Example 1.

[0051] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 98.4%.

[0052] Comparative Example 1:

[0053] The method is basically the same as Example 1, except that thiourea is not added to intercalate the Cu-Al layered bimetallic oxide.

[0054] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of the dried glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 82.9%.

[0055] Comparative Example 2:

[0056] The method is basically the same as Example 1, except that the Cu-Al layered bimetallic oxide is directly added without thiourea intercalation.

[0057] The preparation method of Cu-Al layered bimetallic oxide is as follows:

[0058] 45.3 g of copper nitrate trihydrate and 23.4 g of aluminum nitrate nonahydrate were added to 500 ml of deionized water and stirred to mix evenly. 13.3 g of sodium carbonate was dissolved in 500 ml of deionized water to obtain an alkaline precipitant. The alkaline precipitant was slowly added dropwise to the reaction system to adjust the pH to 9. After the addition, the system was sealed and heated to 110° C. for hydrothermal reaction for 8 h. After the reaction was completed, the system was restored to room temperature. The precipitate was collected and fully washed with anhydrous ethanol and deionized water. The precursor was dried in an oven at 60° C. for 24 h to obtain a precursor. The precursor was placed in a muffle furnace and heated to 550° C. at a rate of 5° C. / min and calcined for 3 h to obtain a Cu-Al layered bimetallic oxide.

[0059] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of the dried glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 91.3%.

[0060] Comparative Example 3:

[0061] The method is basically the same as Example 1, except that no CASB glass powder is added.

[0062] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of the dried glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 94.2%.

[0063] Comparative Example 4:

[0064] The method is basically the same as Example 1, except that CAS glass powder is used instead of CASB glass powder.

[0065] The preparation method of CAS glass powder is as follows:

[0066] CaO, Al2O3 and SiO2 in a mass ratio of 5:15:35 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours on a planetary ball mill and then dried, the obtained mixture is added to a crucible, heated to 1200°C to melt and kept warm for 2 hours to obtain a clarified glass melt, the glass melt is poured into deionized water to obtain glass particles, the glass particles are dried and added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours on a planetary ball mill and then dried through a 400-mesh sieve;

[0067] A 300W xenon lamp was used as the light source and circulating water was used to maintain a constant temperature. 0.05g of the dried glaze was added to 100ml (10mg / L) methylene blue solution. The reaction was allowed to react in the dark for 30min before illumination to ensure adsorption-desorption equilibrium. The xenon lamp was kept 15cm away from the liquid surface. After 60min, 5ml of the solution was centrifuged to obtain the supernatant. The absorbance of the methylene blue solution at 665nm was tested with an ultraviolet spectrophotometer, and the degradation rate was 95.4%.

[0068] Performance Testing:

[0069] The glazes in Examples 1-4 of the present invention and Comparative Examples 1-4 were respectively applied on 95 alumina ceramic substrates with a coating thickness of 10±1 μm, and then the ceramic substrates were dried in an oven at 60° C. for 10 h, placed in a muffle furnace and heated to 1150° C. at a rate of 5° C. / min and sintered for 2 h to obtain test pieces;

[0070] The static contact angle between the specimen surface and water was measured using an SDC-100 contact angle meter.

[0071] Add diatomaceous earth and sodium chloride with a mass ratio of 6:1 into 500ml deionized water to make a dirty liquid. After stirring the dirty liquid evenly, immerse the specimen in it for 24 hours, take it out and drain it, and place it in a cool place for 48 hours. Then place the specimen at 20° with the horizontal plane and turn on the water mist generator to wet it for 15 minutes. After wetting, apply a 5kV DC voltage to both ends of the specimen and measure the current flowing through the surface of the specimen within 1 minute. If the current change during this period does not exceed ±20% of the current average value, it can be considered that the specimen has been wetted for a long time and has reached a wet saturation state. At this time, the current value read from the microammeter is the leakage current value to be measured. The leakage current value is recorded every 10s, and the average value of 5 groups of measurement data is taken as the leakage current of the specimen. The results are shown in Table 1:

[0072] ;

[0073] According to existing research, leakage current plays a leading role in the discharge process on the surface of polluted insulators. Soluble salts, acids, alkalis, etc. on the surface of polluted insulators dissolve in water films to form ionic conductivity, which increases leakage current, thereby significantly reducing surface flashover voltage. When the leakage current is very small, the pollution flashover voltage will be quite large. Therefore, the ceramic insulator prepared by the present invention has excellent anti-pollution flashover performance.

[0074] From the data comparison of Example 1 and Comparative Examples 1 and 2, it can be seen that the addition of thiourea intercalated Cu-Al layered bimetallic oxide plays a positive role in reducing the insulator leakage current and improving the anti-pollution flashover performance;

[0075] From the data comparison between Example 1 and Comparative Examples 3 and 4, it can be seen that the addition of CASB glass powder plays a positive role in reducing the leakage current of the insulator and improving the anti-pollution flashover performance, and Bi2O3 plays a greater role therein.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ceramic insulator, characterized in that: The details are as follows: Cryolite, kaolin, quartz, thiourea intercalated layered bimetallic oxide, glass powder, sodium tungstate, ferrous sulfate and deionized water are ball-milled and mixed evenly, and then a binder is added and stirred to obtain a glaze, and the glaze is applied to a ceramic substrate to obtain a rough blank, and after the rough blank is dried, it is placed in a muffle furnace and heated to 1100-1200°C and sintered for 1-5 hours, and the heating rate during sintering is 1-10°C / min; The preparation method of the thiourea intercalated layered bimetallic oxide is as follows: The layered bimetallic oxide is added to a mixed solvent consisting of dimethyl sulfoxide and deionized water, and the mixture is sealed and heated to 100-110°C and stirred for reaction for 1-5 hours. After the reaction is completed, the precipitate is collected, washed, and dried to obtain a dimethyl sulfoxide intercalated layered bimetallic oxide, which is added to methanol and stirred for reaction for 5-10 days to obtain a methanol intercalated layered bimetallic oxide. Finally, the methanol intercalated layered bimetallic oxide is added to a saturated thiourea methanol solution and reacted in a water bath for 10-20 hours. After the reaction is completed, the product is collected, washed, and freeze-dried at low temperature; The layered bimetallic oxide is a Zn-Al layered bimetallic oxide or a Cu-Al layered bimetallic oxide; The glaze is prepared from the following raw materials in parts by weight: 10-15 parts of cryolite, 20-30 parts of kaolin, 10-15 parts of quartz stone, 5-10 parts of thiourea intercalated layered bimetallic oxide, 5-10 parts of glass powder, 5-10 parts of sodium tungstate, 1-5 parts of ferrous sulfate, 5-10 parts of binder, and 40-60 parts of deionized water; The glass powder is prepared from CaO, Al2O3, SiO2 and Bi2O3 in a mass ratio of 5-10:10-15:30-35:1-5.

2. The method for preparing a ceramic insulator according to claim 1, characterized in that: The volume ratio of dimethyl sulfoxide to deionized water is 10-20:

1.

3. The method for preparing a ceramic insulator according to claim 1, characterized in that: The preparation method of the layered bimetallic oxide is as follows: Add water-soluble zinc salt or water-soluble copper salt, water-soluble aluminum salt to deionized water, add alkaline precipitant to adjust the pH value of the system to 7-10, seal and heat to 110-130°C for hydrothermal reaction for 5-10h, collect the precipitate, wash and dry to obtain a precursor, place the precursor in a muffle furnace, heat to 500-600°C and calcine for 1-5h.

4. The method for preparing a ceramic insulator according to claim 1, characterized in that: The preparation method of the glass powder is as follows: Mix CaO, Al2O3, SiO2 and Bi2O3 and grind them together. Heat them until they are melted to obtain a clear glass melt. Pour the glass melt into deionized water to obtain glass particles. Dry the glass particles and grind them together. Then, pass them through a 400-mesh sieve.

5. The method for preparing a ceramic insulator according to claim 1, characterized in that: The binder is carboxymethyl cellulose and / or polyvinyl alcohol.

Citation Information

Patent Citations

  • Ceramic insulator for high-voltage capacitor and preparation method thereof

    CN116715511A

  • Magnetic magnesium-manganese layered double metal oxide composite and preparation and application

    US20220002167A1